Active, or passive? Revisiting the role of fiscal policy in the great inflation - Stephanie Ettmeier; Alexander Kriwoluzky (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
We reexamine whether pre-Volcker U.S. fiscal policy was active or passive. To do so, we estimate a DSGE model with monetary and fiscal policy interactions employing a sequential Monte Carlo algorithm (SMC) for posterior evaluation. Unlike existing studies, we do not have to treat each policy regime as distinct, separately estimated, models. Rather, SMC enables us to estimate the DSGE model over its entire parameter space. A differentiated perspective results: pre-Volcker macroeconomic dynamics were similarly driven by a passive monetary/passive fiscal policy regime and fiscal dominance. Fiscal policy actions, especially government spending, were critical in the pre-Volcker inflation build-up.
Keywords: C11; C15; E63; E65; 330; Bayesian Analysis; DSGE Models; Monetary-Fiscal Policy Interactions; Monte Carlo Methods